Hydrophilic 3D interconnected network of bacterial nanocellulose/black titania photothermal foams as an efficient interfacial solar evaporator - Nabeela, Kallayi; Thorat, Meghana; Sumina, N. B.; Ramachandran, Animesh M.; Thomas, Reny Thankam; Preethikumar, Gopika; Mohamed, A. Peer; Asok, Adersh; Dastager, Syed Gulam; Pillai, Saju (ACS Applied Bio Materials, 2021)
The design and development of scalable, efficient photothermal evaporator systems that reduce microplastic pollution are highly desirable. Herein, a sustainable bacterial nanocellulose (BNC)-based self-floating bilayer photothermal foam (PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b) is designed that eases the effective confinement of solar light for efficient freshwater production via interfacial heating. The sandwich nanoarchitectured porous bilayer solar evaporator consists of a top solar-harvesting blackbody layer composed of broad-spectrum active black titania (BT) nanoparticles embedded in the BNC matrix and a thick bottom layer of pristine BNC for agile thermal management, the efficient wicking of bulk water, and staying afloat. A decisive advantage of the BNC network is that it enables the fabrication of a lightweight photothermal foam with reduced thermal conductivity and high wet strength. Additionally, the hydrophilic three-dimensional (3D) interconnected porous network of BNC contributes to the fast evaporation of water under ambient solar conditions with reduced vaporization enthalpy by virtue of intermediated water generated via a BNC–water interaction. The fabricated PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b is found to yield a water evaporation efficiency of 84.3% (under 1054 W m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2) with 4 wt % BT loading. Furthermore, scalable PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b realized a water production rate of 1.26 L m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2 h<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1 under real-time conditions. The developed eco-friendly BNC-supported BT foams could be used in applications such as solar desalination, contaminated water purification, extraction of water from moisture, etc., and thus could address one of the major present-day global concerns of drinking water scarcity.